Blood‐based biomarkers of Alzheimer's disease: Standardization and comprehensiveness - Ying Liu; Yu Guo; Jintai Yu (Neuroprotection, 2024)
Abstract Population aging is sweeping across the globe, resulting in a striking prevalence of Alzheimer's disease (AD) and dementia and a heavy economic burden. Given the time window of 10–20 years from pathological initiation to clinically detected cognitive impairment, early detection can significantly impact the prevention and control of AD. The invasiveness and high cost of cerebrospinal fluid biomarkers and positron emission tomography‐computed tomography imaging limit large‐scale disease screening. However, blood‐based biomarkers (BBMs) lack these disadvantages, shedding light on their usefulness in the large‐scale identification and prevention of AD. Prominent advancement has recently been made regarding BBMs of AD co‐pathology (amyloid β, tau protein, neurofilament light polypeptide, and glial fibrillary acidic protein) to improve their accuracy as clinical diagnostics of AD to a level comparable to that of canonical methods, facilitating the large‐scale clinical implementation of diagnostic tests with higher precision. To briefly summarize, the prospects of AD BBMs rely on standardization and comprehensiveness. Calibrating the sample collection procedure and clarifying the boundaries for indices and abnormalities are beneficial for constructing a canonical diagnostic assay. The comprehensive assembly of heterogeneous clinical evidence guarantees the accuracy of diagnosis and improves the workflow for early identification.